1992
DOI: 10.1002/etc.5620110705
|View full text |Cite
|
Sign up to set email alerts
|

Residue‐based interpretation of toxicity and bioconcentration QSARs from aquatic bioassays: Neutral narcotic organics

Abstract: The critical body residue (CBR), estimated from aquatic toxicity QSARs and bioconcentration‐log Kow relationships, appears to be relatively constant, at about 4 mmol L−1 of fish, for the acute toxicity of a variety of hydrophobic narcotic organic chemicals examined by the U.S. Environmental Protection Agency (Duluth, MN) in tests with the fathead minnow. However, for hydrophilic chemicals (log Kow < 1.5) the bulk of the toxicant is in the water phase rather than the organic/lipid phase of the organism, so the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
158
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 62 publications
15
158
1
Order By: Relevance
“…This may possibly be due to the use of higher number of embryos in these assays, leading to an increased statistical power for the detection of differences between the control and nitromusk treatment groups. The concurrently high wholebody concentrations determined via GC-ECD analysis (0.004-0.02 mmol/kg wet weight; Table 1), suggest that the observed mortality may not be due to a specific toxicity mechanism of the nitro-musks tested but rather the result of generalized narcosis, as previously demonstrated for various other organic compounds in fish and amphibians (0.2 -0.8 mmol/kg wet weight; McCarty et al, 1992). This hypothesis is also corroborated by studies of Adema and Langerwerf (1985), who reported musk xylene mediated mortality (LC 50 of 400 mg/l) in zebrafish exposed for 14 days using DMSO as the solvent for musk xylene.…”
Section: Discussionsupporting
confidence: 58%
“…This may possibly be due to the use of higher number of embryos in these assays, leading to an increased statistical power for the detection of differences between the control and nitromusk treatment groups. The concurrently high wholebody concentrations determined via GC-ECD analysis (0.004-0.02 mmol/kg wet weight; Table 1), suggest that the observed mortality may not be due to a specific toxicity mechanism of the nitro-musks tested but rather the result of generalized narcosis, as previously demonstrated for various other organic compounds in fish and amphibians (0.2 -0.8 mmol/kg wet weight; McCarty et al, 1992). This hypothesis is also corroborated by studies of Adema and Langerwerf (1985), who reported musk xylene mediated mortality (LC 50 of 400 mg/l) in zebrafish exposed for 14 days using DMSO as the solvent for musk xylene.…”
Section: Discussionsupporting
confidence: 58%
“…Bioconcentration factors and first-order elimination rate constants for persistent neutral organic compounds in aquatic organisms usually exhibit strong (double logarithmic) relationships with Kow (46)(47)(48)(49)(50)(51)(52). The relationship proposed by Mackay (48) for (wet weight) BCFs in fish commonly is considered a benchmark for the equilibrium partitioning theory (50,(52)(53).…”
Section: Bcf In Relation To Kow the Bcfs Observed For Pahs In A Aqumentioning
confidence: 99%
“…The relationship proposed by Mackay (48) for (wet weight) BCFs in fish commonly is considered a benchmark for the equilibrium partitioning theory (50,(52)(53). The slopes of the wet weight bioconcentration QSARs (quantitative structure-activity relationships) calculated for freshwater isopods show a close resemblance to this benchmark relationship and are in good agreement with slopes documented (Table A-5, SI) for the bioconcentration of PAHs in daphnids and marine mollusks (13,49).…”
Section: Bcf In Relation To Kow the Bcfs Observed For Pahs In A Aqumentioning
confidence: 99%
“…Acute bioassays are useful for analyzing the hazards of highly toxic chemicals and contamination at high levels, but do not test key life-stage events, such as moulting and reproduction, during which organisms' susceptibility to toxicants may increase, and thus they do not show the long-term effects of contaminant exposure at low levels. Alternatively, chronic exposure to low levels of PAHs in sediment is more environmentally relevant (McCarty et al 1992). Fewer data, however, are available regarding toxicity in benthic invertebrates after chronic exposure to PAHs in sediment.…”
mentioning
confidence: 99%